Pitch Strength of Residual Sounds Estimated Through Chroma Recognition by Absolute-Pitch Possessors - Piotr ROGOWSKI; Andrzej RAKOWSKI (Archives of Acoustics)
Absolute pitch is a unique feature of the auditory memory which makes it possible for its possessors to recognize the musical name (chroma) of a tone. Six musicians with absolute pitch, selected from a group of 250 music students as best scoring in musical pitch-naming tests, identified the chroma of residue pitch produced by harmonic complex tones with several lower partials removed (residual sounds). The data show that the percentage of correct chroma recognitions decreases as the lowest physically existent harmonic in the spectrum is moved higher. According to our underlying hypothesis the percentage of correct chroma recognitions corresponds to the pitch strength of the investigated tones. The present results are compared with pitch strength values derived in an experiment reported by Houtsma and Smurzynski (1990) for tones same as those used in this study but investigated with the use of a different method which consisted in identification of musical intervals between two successive tones. For sounds comprising only harmonics of very high order the new method yields a very low pitch recognition level of about 20% while identification of musical intervals remains stable at a level of about 60%.